Leveransförbättringar för effektivare flöden : En studie vid Trafikverket Materialservice - Älgamo, Madeleine (2015)
Logistics is a central concept for companies active in the distribution and storage industry. Logistics can be seen as the science of efficient material flow. Material flows in supply chains take place both internally and by transports between suppliers and customers. It is usually transports that have the greatest negative impact on the environment in a logistic system. Transports also generate costs, which require planning of resources. Planning takes place at different levels and some of the decisions are about striving for increased fill rate in the carrier and consolidation of deliveries. Therefore, coordinated and efficient material- and information flow are highly important.The purpose of the study is to identify and describe issues related to deliveries and the associated material- and information flow. The study also aims to study and analyse how deliveries can be improved for these flows to be more efficient and contribute to a reduced environmental impact. A specific construction project in northern Sweden acted as the reference object to get a deeper understanding of the study's problem.The study was conducted as a case study at Materialservice in Nässjö. Materialservice is a logistics company responsible for securing the supply of railway components secured for a long time. Materialservice has previously been seen as an external supplier, a separate part, but now belongs to Trafikverket. To carry out this study, the data was collected through interviews, observations and literature studies. By collecting data in this way the study's author has been able to create an overall picture of the business to gain a better understanding of the problem area studied. The collected data were the basis for the current situation description, which in turn was the basis for the situation analysis. The situation analysis was created with the help of connections between the current situation description and the theoretical framework. In the current situation analysis, problem areas are identified and analysed by ...